(1493) The optimum production rate in "vehicle fleet scheduling" problems معدل الإنتاج الأمثل في مشاكل "جدولة أسطول المركبات" - Abdel Rahman, Mohammed Yehia (The Institute of National Planning, 2018)
The well known V.F.S problems became one of the classical problems under the assumption that the quantities which were found at the production pointSare fixed and do not depend on time. ' This paper aims at remodifying the problem in a more realistic and applicable mode by assuming that the quantities will increase in a given rate.